Depositional control on the sulfur content and isotope of sedimentary pyrite from the southeast coast of China since MIS5 - Chang, Xin; Liu, Xiting; Wang, Houjie; Zhuang, Guangchao; Ma, Zhixin; Yu, Junjie; Chen, Jing (Frontiers in Marine Science, 2022)
The content and isotopic composition of pyrite sulfur are significantly affected by local depositional conditions and are sensitive to environmental evolution. Here, we use core QK11, collected from Xiapu Bay, southeast coast of China, to reveal how local depositional conditions constrained pyrite formation and sulfur isotopic composition since MIS5. Our results show that the content of pyrite sulfur is mainly controlled by the TOC content during interglacial intervals and is limited by the supplement of sulfate in glacial intervals. Therefore, the C/S ratios can effectively identify three transgressions since MIS5. The sulfur isotopic composition of pyrite ranges from -36.7 to 18.4‰ in the whole core. The occurrence of isotopically “heavy” pyrite is observed at the depth of 2.2~9.2, 27.2~33.8, and 43.5~62.5 mbsf, which is attributed to the influence of sulfate reservoir effect, depositional event, unsteady diagenetic environment, and other factors, highlighting the influence of local depositional and diagenetic processes on the isotopic composition of pyrite sulfur. Pyrite sulfur in other layers is generally depleted in 34S, as low as -36.7‰, indicating that the early-stage organiclastic sulfate reduction (OSR) plays an important role in sulfur isotopic fractionation. The results also suggest that organic carbon indicators (TOC/TN ratio and δ13C) combined with the C/S ratio can effectively distinguish between freshwater and marine environments, which is of great significance to reveal depositional evolution in deep time.